Application of multimodal large language models for safety indicator calculation and contraindication prediction in laser vision correction - Joon Yul Choi; Doo Eun Kim; Sung Jin Kim; Hannuy Choi; Tae Keun Yoo (npj Digital Medicine)
Abstract This study demonstrates the potential of multimodal large language models in calculating safety indicators and predicting contraindications for laser vision correction. ChatGPT-4 effectively analyzed ocular data, calculated key indicators, generated calculator codes, and outperformed traditional machine learning models and indicators in handling unstructured data and corneal topography. Its modality-independent system enabled efficient and accurate data analysis. Despite longer processing times, ChatGPT-4’s performance highlights its potential as a decision-support tool, offering advancements in improving safety.